Posisi Varietas Bersari Bebas dalam Usahatani Jagung di Indonesia - Zubachtirodin Zubachtirodin; Firdaus Kasim (Iptek Tanaman Pangan, 2012)
High yielding maize varieties had contributed significant yield increase in the national maize production. High yielding varieties were established from series of activities on germplasm improvement. The products of maize germplasm improvement are classified into open pollinated variety and hybrid variety. In Indonesia, before the year of 2000 germplasm improvement were focussed on open pollinated variety development, due to its low cost, and the seed can be produced easily, when commercial maize seed industries had not developed. During this period, several open pollinated varieties were released (i.e. Harapan, Arjuna, Kalingga, and Bisma) possesing high yield potential, mid-early maturity, resistance to downy mildew disease, and adaptative to various environments. The OP varieties during those period dominated farmers maize planting area. In the last 10-years, hybrid varieties were developed by commercial maize seed industries, therefore, the use of open pollinated varieties were decreasing. Farmers shifted their interest to high yielding varieties. The OP varieties were less supported by government, and seed production subsystem was weakened. However for the less developed farming interprises, open pollinated varieties are still needed, thus the seeds are distributed in sufficient quantities to the local seed growers. The flow of seeds from the foundation seed, stock seed, to the extension seed, however, is unreliable due to the uncertainty of the markets. In eastern part of Indonesia open pollinated varieties are still played its importance, especially variety Lamuru, Sukmaraga, Srikandi Kuning and Anoman. Strong support from the goverment is needed to establish and develop the seed supply system, including the seed procurement for the seed assistance program.